Manajemen Filsafat Pendidikan Karakter: Filsafat Sebagai Asas Pembentukan Karakter melalui Pendidikan Karakter - Fauzi, Ihwan (Al-Riwayah : Jurnal Kependidikan, 2019)
The nature of character education is carving and painting values into learners through education. This research is descriptive analytical, that is, using expert theories about all matters relating to character education, then analyzing it so that the essence of philosophy can be found in forming good personalities through character education. The things that will be examined are whether character and character education, philosophical foundation, human nature in character education, character building strategies, forming characters starting from oneself and family so that the aim of this research is to understand the formation of good personality through character education can be accomplished by the optimization of aspects (power) that there are aspects of reason (cognitive) aspects of affective (spiritual) and motoric aspects (physical). Islamic education is a process of approach to help humans to reach the level of perfection that is humans who reach the height of faith and knowledge aimed at good deeds means that the process of Islamic education must be directed in order as a generator and digger of human potential.